2022
DOI: 10.1371/journal.ppat.1010584
|View full text |Cite
|
Sign up to set email alerts
|

Insight into mechanisms of pig lncRNA FUT3-AS1 regulating E. coli F18-bacterial diarrhea

Abstract: Escherichia coli F18 is a common conditional pathogen that is associated with a variety of infections in humans and animals. LncRNAs have emerged as critical players in pathogen infection, but their role in the resistance of the host to bacterial diarrhea remains unknown. Here, we used piglets as animal model and identified an antisense lncRNA termed FUT3-AS1 as a host regulator related to E. coli F18 infection by RNA sequencing. Downregulation of FUT3-AS1 expression contributed to the enhancement of E. coli F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Furthermore, these DEGs were enriched in 20 pathways, including 41 significantly enriched Toll-like receptor signaling pathways (i.e., p < 0.05) (see Supplementary Table S3 ). Among them, the pathway of the “Glycosphingolipid biosynthesis-lacto and neolacto series” (ko00940) was enriched in the shFUT8 and shNC samples ( Figure 4 D), which probably played an important role in the regulation of E. coli F18 receptor formation [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these DEGs were enriched in 20 pathways, including 41 significantly enriched Toll-like receptor signaling pathways (i.e., p < 0.05) (see Supplementary Table S3 ). Among them, the pathway of the “Glycosphingolipid biosynthesis-lacto and neolacto series” (ko00940) was enriched in the shFUT8 and shNC samples ( Figure 4 D), which probably played an important role in the regulation of E. coli F18 receptor formation [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported the involvement of dysregulated lncRNAs in the regulation of infectious diarrhea in domestic animals. For instance, porcine lncRNA FUT3-AS1 regulates Escherichia coli F18 susceptibility through histone H4 modification or the miR-212/FUT3 axis [ 26 ]. The porcine endemic diarrhea virus infection affects the expression of lncRNAs in the ileum of piglets and is linked to the activation of the immune system in the same region [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies demonstrated that lncRNAs play an essential role in host resistance to bacterial diarrhea. For instance, lncRNA FUT3-AS1 silencing enhanced resistance to Escherichia coli F18 in IPEC-J2 cells [ 43 ]. lncRNA IALNCR knockdown exerted antiviral functions through MAPK8/JNK1 pathway to promote Bovine viral diarrhea virus (BVDV) infection-generated apoptosis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%